2014
DOI: 10.1289/isee.2014.p3-746
|View full text |Cite
|
Sign up to set email alerts
|

Human Aflatoxin Exposure in Kenya, 2007: a Cross-Sectional Study

Abstract: Aflatoxins contaminate approximately 25% of agricultural products worldwide. They can cause liver failure and liver cancer. Kenya has experienced multiple aflatoxicosis outbreaks in recent years, often resulting in fatalities. However, the full extent of aflatoxin exposure in Kenya has been unknown. Our objective was to quantify aflatoxin exposure across Kenya. We analysed aflatoxin levels in serum specimens from the 2007 Kenya AIDS Indicator Surveya nationally representative, cross-sectional serosurvey. KAIS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
(30 reference statements)
2
16
0
Order By: Relevance
“…There are conflicting evidence for associations between wealth and AF exposure in prior studies. Four studies investigated the sociodemographic determinants of AF exposure: two (Kenya and Ghana) reported lower AF exposure in higher‐income households and two (also Kenya and Ghana) reported no relationship . Although AF exposure did not vary across wealth quintiles, it is possible that the pathways to exposure vary among economic subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting evidence for associations between wealth and AF exposure in prior studies. Four studies investigated the sociodemographic determinants of AF exposure: two (Kenya and Ghana) reported lower AF exposure in higher‐income households and two (also Kenya and Ghana) reported no relationship . Although AF exposure did not vary across wealth quintiles, it is possible that the pathways to exposure vary among economic subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the AF-alb biomarker has revealed high aflatoxin exposure in East African countries including Kenya 14) , where AF-alb was detected in 78% of 597 serum samples (non detectable (ND) − 211 pg/mg); in Uganda 15) , where AF-alb was detected in 192/196 (98%) samples (range ND to 237.7 pg/mg) collected from adults and children; and in Tanzania 16) , where AF-alb was detected in 67% to 99% of samples collected from young children (see Table 1 for more details). In North and South Africa, where the climate is drier, the prevalence of aflatoxin exposure is lower than the levels observed in East and West Africa [17][18][19] .…”
Section: Worldwide Aflatoxin Exposurementioning
confidence: 99%
“…Lastly, different researchers use different methods of sample analysis. Some have argued that the HPLC method for detecting aflatoxin levels is less sensitive than the ELISA and liquid chromatography with tandem mass spectrometry methods (McCoy et al, ), and Yard et al () found that the estimated AFB1‐lysine adduct values from the ELISA method are typically 4.6 times higher than those from the HPLC‐fluorescence measurement (Yard et al, ). As a result, aflatoxin levels differing across studies may also stem from differences in the laboratory method used, which should be noted when interpreting the results.…”
Section: Discussionmentioning
confidence: 99%